Christianity in Thrace and Moesia before the emergence of the imperial church - Hošek, Radislav (Balcanica Posnaniensia. Acta et studia, 1990)
The article analyzes the development of Christianity in Thrace and Moesia before its recognition as a state religion. The problem concerns the difficulty of reconstructing the early history of Christianity due to the limited source base. The aim of the work is to present the process of the spread of the new religion and its organizational structures. The author uses analysis of written sources and hagiographic tradition. The most important results indicate that Christianity developed from the 2nd century, and a turning point was the Edict of Milan in 313, which legalized the religion. The earlier period is known mainly from martyrological tradition, which indicates numerous persecutions and a significant number of martyrs in the region. The author also discusses missionary routes (e.g., the activity of Paul) and the development of church organization and the monastic movement. The conclusion emphasizes the importance of Thrace and Moesia as important areas of early Christianity despite the fragmentary nature of sources.